MODELLING OF ELECTRODEPOSITION BATH USING THE FLOW ANALYSIS TECHNIQUE - Budak, T. B.; Koyuncu, I.; Akcin, G.; Afsar, H. (WALTER DE GRUYTER GMBH, 2009)
This study aims to develop coating quality by using Flow Analysis (FA) technique in acid copper coating bath. The coating metal concentration of electrodeposition bath mixture, current density, coating time, distance between anode and cathode, temperature of bath mixture and pH are some of the factors which affect the coating quality. The coating metal concentration is the most important parameter. The metal concentration of electroplating bath solution decreases during the coating so coating quality also decreases. Bath mixture composition has been determined by analysing samples periodically according to the conventional industrial application. Much more time, effort and high financial cost are very necessary for this type of analysis. This paper represents a new method which determines the metal concentration of coating baths with flow analysis technique. The metal concentration is measured on-line with spectrophotometric technique which includes flow through cell according to the new method. This technique is very simple and the results can be taken easily. Firstly, the decrease in metal concentration is determined by the batch technique and then a sufficient amount of stock metal solution is added to the plating bath continuously by on-line system. The metal concentration of coating bath solution is kept at constant concentrations. This means that the coating metal quality does not decrease. All data are examined statistically. After reaching optimum conditions, coating results are examined by using Faraday Laws.
Keywords: Copper (II); Electroplating; Current Density; On-Line; Electrodeposition; Flow Through Cell; INJECTION ANALYSIS; Chemistry